PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP PROFITABILITAS (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) (Diponegoro Journal of Accounting, 2022)
The objective of this research is to examine the effect of Green Accounting implementation towards profitability. Variabel used in the examination are profitability as a dependent variable and environmental performance and environmental disclosure as independent variable. The population in this study is a manufacturing company in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2017 until 2020. Purposive sampling method is used in this research with sample results from 48 companies. The data used in this study is secondary data in the form of annual reports and sustainability reports from 2017 until 2020.  The analysis method of this research used multiple linear regressions. This research result shows environmental performance has influence on profitability, whereas environmental disclosure does not influence profitability.